Sex differences in blood‐based biomarkers in individuals with autosomal dominant Alzheimer's disease. (1st February 2022) - Vila‐Castelar, Clara; Lopera, Francisco; Zetterberg, Henrik; Hansson, Oskar; Dage, Jeffrey L; Janelidze, Shorena; Chen, Yinghua; Su, Yi; Garcia, Gloria; Aguillon, David; Baena, Ana Y.; Giraldo‐Chica, Margarita; et al.
Abstract: Background: Blood‐based biomarkers are a promising tool for early detection of Alzheimer's disease (AD). We recently showed that individuals with autosomal‐dominant AD due to the E280A mutation in the presenilin1 gene ( PSEN1 ) showed elevated levels of plasma tau phosphorylated at threonine 217 (P‐tau217) and neurofilament light chain (NfL), as early as approximately 20 years before clinical onset. We examined sex differences in the age‐related trajectory of these blood‐based biomarkers, and whether they predicted cognitive performance in PSEN1 mutation carriers. Method: Cross‐sectional plasma P‐tau217 and NfL concentrations were measured using highly sensitive immunoassays from 622 participants, including 259 cognitively‐unimpaired mutation carriers (mean age: 31, range 24‐39; %male: 45.6), 106 cognitively‐impaired mutation carriers (mean age: 49, range 46‐52; %male: 45.3), and 257 age‐matched noncarriers (mean age: 34, range 25.5‐42; %male: 39.3). Bivariate local polynomial regressions (LOESS) were used to characterize relationships between log‐transformed P‐tau217 and NfL with age. Linear mixed effect models were used to estimate the fixed slope and intercept of female and male among carriers and noncarriers. Linear regressions examined the association between blood biomarkers and CERAD word list delayed recall in mutation carriers. Result: There were no sex differences in the association between age and plasma P‐tau217 among mutation carriers (Slope test, p =.055). Female carriers showed a steeper slope for the association between age and plasma NfL, compared to male carriers (Slope test, p =.001). There was a significant interaction between sex and plasma NfL in predicting verbal memory delayed recall ( b =.020, p =.000) in mutation carriers. No sex differences were observed in the association between age and any blood biomarkers among noncarriers (Slope tests: NfL, p =.963; P‐tau271, p =.867). Conclusion: Our findings indicate that there are no sex differences in plasma tau pathology in PSEN1 carriers and noncarriers. However, female carriers showed greater levels of plasma NfL along their age‐related trajectory, compared to male carriers, suggesting that female carriers may be more susceptible to AD‐related neurodegeneration. Further research examining sex/gender differences in blood‐based biomarkers and its relation to cognitive trajectories is needed to understand mechanisms of resilience and susceptibility in AD.